Ultraman. 11, The legend still lives in the light of justice - Shimizu, Eiichi, 1978-; Shimoguchi, Tomohiro, 1978-; Stan!, 1964- (Viz signature., 2019)
Shinjiro, Moroboshi, Hokuto, Jack, Taro, and even Shin Hayata--the first Ultraman--have all come together in New York City for the ultimate showdown with the forces of the Star of Darkness! Can Moroboshi's brother be saved? Will the idol Rena Sayama make it through this all-out battle? And what is the Star of Darkness's ultimate plan? The winners will know the answers...